A Mathematical Programming Approach to a Deterministic Kanban System - Bitran, Gabriel R.; Chang, Li (Management Science, 1987)
In this paper we present a mathematical programming model for the Kanban system in a deterministic multi-stage capacitated assembly-tree-structure production setting. We discuss solution procedures to the problem and address three special cases of practical interest.